The Authentic Art of the Situationist International (Itinera, 2016)
To conceive an art which was able to change everyday life was the main aim of Situationism, an artistic avant-garde active in the Europe of the 60s. The Situationism’s members tried to get the realization and suppression of art through the use of détournement. As a result they got a baroque aesthetic instead of a modern one.